Pluralis dan Pluralisme dalam Perspektif - Teng, H.Muhammad Bahar Akkase (JURNAL ILMU BUDAYA, 2015)
In this paper, we will discuss about Pluralist and Pluralism in HistoricalPerspective.Pluralism is an understanding, which is historically was not brought by Moslem but from Christian. In 1527 AD, The St. Barthalomens Day‘s Massacre was occured in Paris. 10,000 people of Protestant people were killed by Catholic people. This type of events then inspire Catholic Theology Revision on Vatican Council II (1962-1965 AD). Thus, religion pluralism have no root in Islam history and tradition.Pluralism is seen on many perspectives, such as in Cultural philosophy perspective, Social perspective, Religion perspective.The adoption of religion pluralism factors are:(1)Democracy,(2)Pragmatisme,(3)Relativism, (4)Perennialism.Pluralism in religion can be understood by three categorizes: (a)Social category, (b)Moral and Ethic category, (c)Theology-Phylosophy category. Religion outlook on pluralism.From Hindu,truth is exist and can be found in all of the religions. From Christian (Catholic), they understand that exclusivism of truth should be banned(―ownself religion is true‖ is a vanity).Many Protestant theologist are founder of religion pluralism.However, there are many protests about religion pluralism from protestan themselves.On July 28th, 2005, Indonesian Religious Leader (Majelis Ulama Indonesia, MUI)Pada tanggal 28 Juli 2005, MUI issued a fatwa which forbids pluralism.Thus, MUI stated that pluralism, in the context, contrary to Islam. The inception of various religion pluralism thoeries. The reason of variousity is differences of cultures produce different real opinion. There are two factors of those occurrence, which are: Internal factor (ideology; beliefs and desireability) and External factor. While, theexternal factor can be classified on to: Socio-politic factor, Scientific factor, and technology factor.Keywords :Pluralist, Pluralism, Inception and History